Во славу Отечества! - Белогорский Евгений Александрович (Говорящая книга для слепых, 2020)
Экземпляры: БС (20200921) / Инвентарный номер: ФК2695 / Цена: / Сис.шифр: 84(2) / Авт.знак: Б 43 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4